Fundamental Studies of a Three Phase Cascaded H-Bridge and Diode Clamped Multilevel Inverters Using Matlab/Simulink - Omar, Rosli; Rasheed, Mohammed; Sulaiman, Marizan (Praise Worthy Prize, 2013)

(untitled)
This paper presents a fundamental study of two type’s multilevel inverters comprising of Cascaded H-Bridge and Diode Clamped for harmonic reduction for high power applications. The application of multilevel inverters is capable to minimize the number of harmonic contents in low voltage electrical distribution system. This study discusses a three phase comparative analysis between multi-level circuits diode clamped inverter and cascaded H-Bridge inverter with sinusoidal pulse width modulation (SPWM) strategies. Nine levels SPWM inverter with switching functions are used for the operating principles to alleviate harmonic components of the output voltage of multilevel inverters. Simulation results show that the Total Harmonics Distortion for voltage (THDV) of the output for the both multilevel inverters are decreased and have been achieved lower contents based on IEC standard.